Modelling and experimental analysis of aero-engine performance and exhaust emission characteristics fueled with green fuel blends - Abu Talib, Abd Rahim; S. M. Altarazi, Yazan; Yu, Jianglong; Gires, Ezanee; Fahmi Abdul Ghafir, Mohd; Tahmasebi, Arash; Yusaf, Talal; Alsultan, Abdulkareem G.; Yunus, Robiah (Elsevier Ltd, 2024)
This study aims to assess the impact of using green fuel in place of biodiesel on the performance and exhaust emissions of air-breathing engines. GasTurb 13 is utilized to forecast the engine's performance (kingTech 180 k turbojet engine). Catalytic deoxygenation of vegetable oils produces green diesel, offering an alternative to biodiesel. Physiochemical properties of GD blends (PME30GD20, PME20GD30, PME10GD10) were analyzed, and GasTurb-13 software predicted engine performance and emissions, validated with experimental data. The results show that GD10PME10 exhibited higher density (767.6 g/m3) than pure green fuel, while viscosity dropped by 53.85 % compared to PME. GD outperformed Jet-A1 by 0.74 % in heating value, with GD10PME10 having the highest at 42.63 MJ/kg. Engine performance measures included thrust, mass fuel flow, thrust-specific fuel consumption, and exhaust gas temperature. GD10PME10 showed a 12.5 % thrust increase and the lowest TSFC (95 g/kN.s) at 80,000 RPM compared to Jet-A1. GD20PME30 achieved the lowest EGT (550 °C) at the same RPM. Regarding emissions, GD20PME30 emitted the lowest CO (100,000 RPM, 150 ppm) and 0.5 % less CO2 (90,000 RPM) than Jet-A1. GD10PME10 produced the lowest NOx (12.5 ppm) at maximum speed, while Jet-A1 emitted the least NOx (7.5 ppm) at 120 k RPM. Overall, the data suggested that green fuel might increase the physiochemical properties of biodiesel blends, hence improving the fuel's capacity to burn more effectively in aero-engines.